Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1101/gad.255331.114
|View full text |Cite
|
Sign up to set email alerts
|

The E–Id protein axis modulates the activities of the PI3K–AKT–mTORC1–Hif1a and c-myc/p19Arf pathways to suppress innate variant TFH cell development, thymocyte expansion, and lymphomagenesis

Abstract: It is now well established that the E and Id protein axis regulates multiple steps in lymphocyte development. However, it remains unknown how E and Id proteins mechanistically enforce and maintain the naïve T-cell fate. Here we show that Id2 and Id3 suppressed the development and expansion of innate variant follicular helper T (T FH ) cells. Innate variant T FH cells required major histocompatibility complex (MHC) class I-like signaling and were associated with germinal center B cells. We found that Id2 and Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 61 publications
0
57
0
Order By: Relevance
“…Thus, it appears that the regulation of Ccr6 by the E2A/Id3 axis is conserved between human and murine germinal center B cells. More recent studies have indicated that depletion of both Id2 and Id3 expression in T lineage cells leads to the rapid development of T cell lymphoma (20). Is Id3 expression also essential to suppress the development of lymphoma in mice?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it appears that the regulation of Ccr6 by the E2A/Id3 axis is conserved between human and murine germinal center B cells. More recent studies have indicated that depletion of both Id2 and Id3 expression in T lineage cells leads to the rapid development of T cell lymphoma (20). Is Id3 expression also essential to suppress the development of lymphoma in mice?…”
Section: Discussionmentioning
confidence: 99%
“…ϩ innate ␥␦ T cells, and innate variant T FH cells (20)(21)(22)(23)(24)(25)(26). The intrinsic roles of Id proteins in B cell development have not been examined in great detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized is the negative regulatory mechanism involving expression of Drosophila Emc or mammalian Id, which contain an HLH domain but no DNA-binding domain: Emc/Id forms a heterodimer with E that cannot bind DNA, thereby acting as dominant-negative to reduce E activity (Benezra et al 1990;Ellis et al 1990). Id regulates E in diverse developmental and physiological processes, and how it regulates E continues to be investigated (Ling et al 2014;Miyazaki et al 2015). In addition, in some contexts, E proteins may stabilize their dimerization partners (Viñals et al 2004;Roark et al 2012).…”
mentioning
confidence: 99%
“…However, after a presumed second hit, lymphoma cells have enrichment for genes often dysregulated in cancers, cytokine-cytokine interaction genes and Nf-κB signaling, similar to pathways reported in human NK/T tumors. Similarly, deficiency of Id2 and/or Id3 in mice also causes an expansion of innate variant T FH -like cells, and ab T cell lymphomas in these Id2/Id3-deficient mice that display an increase in Myc expression and reduction in the tumor suppressor Cdkn2a [88,110]. There is evidence to suggest tumor suppressor functions of Id4 in T cell tumors.…”
Section: Paradoxical Role Of Id Proteins In T Cell Lymphomasmentioning
confidence: 98%